2016
DOI: 10.1038/nn.4465
|View full text |Cite
|
Sign up to set email alerts
|

An independent, landmark-dominated head-direction signal in dysgranular retrosplenial cortex

Abstract: We investigated how landmarks influence the brain’s computation of head direction and found that in a bi-directionally symmetrical environment, some neurons in dysgranular retrosplenial cortex showed bi-directional firing patterns. This indicates dominance of neural activity by local environmental cues even when these conflict with the global head direction signal. It suggests a mechanism for associating landmarks to or dissociating them from the head direction signal, according to their directional stability/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
290
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(337 citation statements)
references
References 18 publications
29
290
1
Order By: Relevance
“…The latter have been shown to switch between active and inactive states, providing a directional representation that is controlled by visual landmarks instead of attractordynamics (Kornienko et al, 2018). Our present results are in line with the function and the location of these sensory HD-cells found in the entorhinal and parahippocampal cortex (Kornienko et al, 2018) as well as potentially in the RSC (Jacob et al, 2017). Some of these cells also alternate between several preferred directions depending on context, potentially explaining the variation in RSC tuning width we observed (Fig.…”
Section: Visual Information and Head Directionsupporting
confidence: 91%
See 1 more Smart Citation
“…The latter have been shown to switch between active and inactive states, providing a directional representation that is controlled by visual landmarks instead of attractordynamics (Kornienko et al, 2018). Our present results are in line with the function and the location of these sensory HD-cells found in the entorhinal and parahippocampal cortex (Kornienko et al, 2018) as well as potentially in the RSC (Jacob et al, 2017). Some of these cells also alternate between several preferred directions depending on context, potentially explaining the variation in RSC tuning width we observed (Fig.…”
Section: Visual Information and Head Directionsupporting
confidence: 91%
“…We observed that multiple brain areas encoded direction, many of which overlap with regions known to contain HDcells in rodents and monkey. These regions include the RSC (Chen et al, 1994;Cho and Sharp, 2001;Jacob et al, 2017), the postsubiculum (part of the hippocampal formation) (Taube et al, 1990) and the entorhinal cortex (EC) (Giocomo et al, 2014;Kornienko et al, 2018;Sargolini et al, 2006). The latter consists of at least two subdivisions in rodents, the medial (MEC) and the lateral entorhinal cortex (LEC), likely corresponding to the pmEC and alEC in humans (Maass et al, 2015;Navarro Schröder et al, 2015).…”
Section: Visual Information and Head Directionmentioning
confidence: 99%
“…One explanation could be that visual cues might be more salient for the vertical axis compared to the horizontal axis. Within the HD system, RSC is directly connected to early visual cortex (Kobayashi & Amaral, ) and HD cells in RSC are dominated by local visual landmarks (Jacob et al, ). Of note, presubiculum is also known to have direct connections with V2 in rodents (Vogt & Miller, ), but we are not aware of direct connections between the presubiculum and early visual cortex in primates.…”
Section: Discussionmentioning
confidence: 99%
“…RSC neurons have further been shown to 68 encode context as well as task-related cues such as goal location ( RSC and visual cortex. Finally, a subset of cells in RSC encode head direction in a way 73 that is particularly sensitive to local environmental cues (Jacob et al, 2017). A common 74 theme across these studies is the importance of visual inputs for RSC function.…”
Section: Introduction 23mentioning
confidence: 99%